Pengaruh Gaya Desain Gotik dan Kolonial Belanda Terhadap Efek Pencahayaan Alami pada Gereja Katolik Hati Kudus Yesus di Surabaya - Santoso, Dewi Sri Maryati (Institute of Research and Community Outreach - Petra Christian University, 2014)
Hati Kudus Yesus Catholic Church in Surabaya influenced Gothic and Dutch Colonial style, which have different views in the processing of natural lighting. This research aims to fine out the applied of Gothic and Dutch Colonial design style and itsinfluenceto natural lighting effect in the church.This type of research is qualitative research. Results of research showed that the processing of natural lighting in the church is not only focuses on the aspect of function but also the embodiment of spiritual atmosphere, although there are still areas with inadequate lighting conditions (less comfortable).